Komparasi Multilevel Inverter Satu Fasa - Irma Husnaini; Asnil Asnil; Habibullah Habibullah; Krismadinata Krismadinata (Fakultas Teknik, Universitas Brawijaya, 2019)
Abstract— This paper discusses multilevel single-phase inverters to improve voltage quality by reducing harmonics. In order to see the performance of multilevel single-phase inverters in reducing the output voltage harmonics, a comparison of several single-phase multilevel inverters with a multilevel H-bridge topology is performed. Increasing the voltage level on the multilevel inverter will reduce harmonics such that losses will be significantly reduced. Multilevel single phase inverter simulation is performed for three-level, five-level and seven-level inverters using matlab/simulink software. The simulation results show that the Total Harmonic Distortion (THD) output voltage of five levels single phase inverter is smaller than three-level inverter and THD output voltage of the seven levels inverter is smaller than using a five-level single phase and three-level inverter, where the THD can be reduced to 13 45%. Index Terms— multilevel single phase inverter, harmonics, THD. Abstrak–- Tulisan ini membahas tentang multilevel inverter satu fasa untuk memperbaiki kualitas tegangan dengan mengurangi harmonisa. Untuk melihat kinerja multilevel inverter satu fasa dalam mereduksi harmonisa tegangan keluaran dilakukan perbandingan beberapa multilevel inverter satu fasa dengan topologi jembatan-H bertingkat. Peningkatan level tegangan pada multilevel inverter akan mengurangi harmonisa akibatnya rugi-rugi akan berkurang secara signifikan. Simulasi multilevel inverter satu fasa dilakukan untuk inverter tiga tingkat, limatingkat dan tujuh tingkat menggunkana software matlab/simulink. Hasil simulasi memperlihatkan Total Harmonic Distortion (THD) tegangan keluaran inverter satu fasa lima tingkat lebih kecil dibandingkan dengan inverter tiga tingkat dan THD tegangan keluaran inverter tujuh tingkat lebih kecil dibandingkan menggunakan inverter satu fasa lima tingkat dan tiga tingkat, dimana THD nya dapat direduksi menjadi 13,45%. Kata Kunci— multilevel inverter satu fasa, harmonisa, THD.